The poetics of palliation : romantic literary therapy, 1790-1850 - Pladek, B. (Liverpool University Press, 2019)
The Poetics of Palliation argues that Romanticism developed richer literary therapies than its contemporary reception remembers. By reading Romantic writers against Georgian medical ethics, Poetics recovers their models of literature as comfort and sustenance, challenging a health humanities tradition that sees literary therapy primarily as cure.
Keywords: Literature and medicine -- Great Britain -- History -- 18th century.; Literature and medicine -- Great Britain -- History -- 19th century.; Literature, Modern -- Appreciation -- Great Britain -- History -- 18th century.; Literature, Modern -- Appreciation -- Great Britain -- History -- 19th century.; Psychology and literature -- History -- 18th century.; Psychology and literature -- History -- 19th century.; English literature -- 18th century -- History and criticism.; English literature -- 19th century -- History and criticism.; Romanticism -- Great Britain.; Littérature et médecine -- Grande-Bretagne -- Histoire -- 18e siècle.; Littérature et médecine -- Grande-Bretagne -- Histoire -- 19e siècle.; Psychologie et littérature -- Histoire -- 18e siècle.; Psychologie et littérature -- Histoire -- 19e siècle.; Littérature anglaise -- 18e siècle -- Histoire et critique.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Romantisme -- Grande-Bretagne.; Literary studies: c 1800 to c 1900.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; English literature; Literature and medicine; Literature, Modern -- Appreciation; Psychology and literature; Romanticism; Great Britain; 1700-1899; health humanities; history of medicine; Romantic poetry; disability studies; New Criticism; Criticism, interpretation, etc.; History